The Yeast Hsp70 Cochaperone Ydj1 Regulates Functional Distinction of Ssa Hsp70s in the Hsp90 Chaperoning Pathway. Issue 3 (1st July 2020) - Gaur, Deepika; Singh, Prashant; Guleria, Jyoti; Gupta, Arpit; Kaur, Satinderdeep; Sharma, Deepak
Abstract: Heat-shock protein (Hsp) 90 assists in the folding of diverse sets of client proteins including kinases and growth hormone receptors. Hsp70 plays a major role in many Hsp90 functions by interacting and modulating conformation of its substrates before being transferred to Hsp90s for final maturation. Each eukaryote contains multiple members of the Hsp70 family. However, the role of different Hsp70 isoforms in Hsp90 chaperoning actions remains unknown. Using v-Src as an Hsp90 substrate, we examined the role of each of the four yeast cytosolic Ssa Hsp70s in regulating Hsp90 functions. We show that the strain expressing stress-inducible Ssa3 or Ssa4, and the not constitutively expressed Ssa1 or Ssa2, as the sole Ssa Hsp70 isoform reduces v-Src-mediated growth defects. The study shows that although different Hsp70 isoforms interact similarly with Hsp90s, v-Src maturation is less efficient in strains expressing Ssa4 as the sole Hsp70. We further show that the functional distinction between Ssa2 and Ssa4 is regulated by its C-terminal domain. Further studies reveal that Ydj1, which is known to assist substrate transfer to Hsp70s, interacts relatively weakly with Ssa4 compared with Ssa2, which could be the basis for poor maturation of the Hsp90 client in cells expressing stress-inducible Ssa4 as the sole Ssa Hsp70. The study thus reveals a novel role of Ydj1 in determining the functional distinction among Hsp70 isoforms with respect to the Hsp90 chaperoning action.